The Effect of Beverages, Mouthrinse Solutions and Toothpastes on Color Stability of the Compomer Resin - Ozmen, B.; Nayir, Y. (Cumhuriyet University Faculty of Dentistry cumhuriyetdentj@hotmail.com, 2018)
Objective: The purpose of this study was to evaluate the color stability of compomer resins which exposure to different beverages, mouth rinse solutions and toothpastes. Material and Methods: For beverages, mouth rinse solutions and toothpastes were created 5 sub-groups. All samples used in this study were prepared according to the manufacturer's instructions in the form of discs with a diameter of 10 mm and a height of 2 mm. Same brand and same color tone compomers (Voco, Glasiosite Caps, A2) were used. After the polymerization, all samples were polished with 600, 800 and 1000 grit silicon carbide papers on an abrasive machine under running water. All samples were incubated in distilled water for 24 hours at 37 °C. The samples divided into three sub-groups (Group 1: beverages, Group 2: mouth rinse solutions and Group 3: toothpastes). Samples in group 1 were incubated in 5 different beverages and samples in group 2 were incubated in 5 different mouth rinse solutions for 24 hours at 37 °C. Brushing of the samples (Group 3) were done by the same operator over 2 minutes, twice a day for 4 weeks. The color values of all groups were measured with a spectropfotometer before and after exposure to applications. Results: All samples displayed color changes after applications (ΔE= 0.71 - 5.09), and there was a statistically difference among sub-groups of beverages, mouth rinse solutions and toothpastes (p < 0.05). Conclusion: Beverages and toothpastes that produce a higher color change than the clinically acceptable value (ΔE=3.3) should be used more carefully. Further clinical investigations are needed. © 2018 Cumhuriyet University Faculty of Dentistry.
Kompomer Rezinin Renk Stabilitesine İçeceklerin, Ağız Çalkalama Solüsyonlarının ve Diş Macunlarının Etkisi
Keywords: Beverages; Color Stability; Compomer Resin; Mouth Rinse Solution; Toothpaste